Comparative analysis of blind methods for additive noise variance evaluation in images - Abramova, Victoriya; Abramov, Sergey; Lukin, Vladimir; Zelensky, Alexander (Видавництво Львівської політехніки, 2012)
The comparative analysis for three blind methods for additive noise variance evaluation in images is carried out. Cases of spatially uncorrelated and correlated noise are considered.
Keywords: variance evaluation; blind methods